Comparison of intraperitoneal instillation of ropivacaine with normal saline in laparoscopic cholecystectomy - Bindra, Tripat Kaur; Chawla, Davinder; Kumar, Parmod; Parul, . (International Journal of Research in Medical Sciences, 2017)
Background: Local anesthetics are now widely used, as they have a good safety profile and are available in long acting preparation. They provide the benefit of analgesia without systemic side effects that may result from use of enterally and parenterally administered drugs. Methods: This prospective randomized double-blind study was conducted on 100 patients with symptomatic gall stones disease undergoing laparoscopic cholecystectomy. Patients were randomized to receive either 0.5% of 3mg/kg of Ropivacaine diluted in 100 ml NS, instillation at intraperitoneal space before creation of pneumoperitoneum (group I) or 100 ml NS instillation at intra peritoneal space before creation of pneumoperitoneum (group II). VAS score for pain abdomen as well as shoulder were recorded postoperatively at various time intervals and compared in both the groups. Total analgesic consumption in 24hrs was also noted and compared. Results: The mean postoperative VAS score for abdomen and shoulder pain was significantly (p values<0.05) lower in group I than in group II till 24 hrs postoperatively. The latency time from end of operation to first analgesic requirement was significantly longer in group I than in group II. Conclusions: Intraperitoneal instillation of Ropivacaine before the creation of pneumoperitoneum significantly decreased the total abdominal pain, shoulder tip pain with lower analgesic consumption. As it is safe and without apparent side effects, we believe that intraperitoneal instillation of local anaesthetic in patients undergoing elective laparoscopic cholecystectomy is an effective modality for postoperative pain management.